Method for determining printing parameters of 3D printing sand mold
By printing the eight-character test blocks and establishing mathematical models, the optimal liquid spray volume and laying thickness parameters were determined, and the problem of 3D printing of sand-type strength was solved, and the uniformity and mass stability of sand-type strength were achieved.
Patent Information
- Application Number
- CN202411340005.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The existing 3D printing sand type strength evaluation method cannot accurately consider the strength differences of sand type in different printing directions, resulting in unstable quality and prone to internal defects or fractures.
By printing two eight-character test blocks, detecting their tensile strength ratios, establishing a mathematical model of sand strength and printing parameters, using single-factor control variable method and linear fitting, the best liquid spray volume and laying thickness parameters are determined, so as to make The strength of the sand type is close to the same in different directions.
It realizes isotropy of sand-type strength, improves controllability and quality stability of the 3D printing process, and reduces the occurrence of sand-type fracture and other problems.
Smart Images

Figure CN119282029A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of casting technology, and in particular to a method for determining printing parameters of a 3D printing sand mold. Background Art
[0002] 3D printing (also known as additive manufacturing) is an emerging revolutionary manufacturing technology. It is a process that uses three-dimensional model data as the basis to accumulate materials layer by layer to make objects. 3D printing does not require molds, can be quickly formed, and can produce complex geometric configurations. It has the characteristics of integrating the material preparation process with the part forming process. In recent years, 3D printing sand molds have been increasingly used in casting production.
[0003] However, unlike traditional sand molding methods, 3D printed sand molds are formed by stacking layers, which results in anisotropy in the strength of the sand mold, that is, the sand molds printed with the same parameters have different strengths in different directions. The traditional molding method uses the method of overall solidification molding, so the strength in different directions is consistent.
[0004] From the above, it can be seen that the strength of the sand mold obtained by 3D printing is anisotropic, and the existing acceptance process and evaluation method of the sand mold strength do not take into account the differences in the sand mold strength in different printing directions. The accuracy of evaluating the strength of the 3D printed sand mold is low, and it cannot provide guidance for the selection of the best process parameters for 3D printing, nor can it quickly and accurately determine the appropriate printing parameters to achieve isotropy of the sand mold strength; in actual application, the uneven and uncontrollable strength of the sand mold in all directions will directly lead to quality instability, and internal defects and fractures are prone to occur. Summary of the invention
[0005] In view of the above analysis, the present invention aims to provide a method for determining printing parameters of 3D printing sand molds, so as to solve the technical problems that the prior art cannot accurately evaluate and accept the strength of 3D printed sand molds, and it is difficult to quickly obtain the optimal printing parameters.
[0006] The purpose of the present invention is mainly achieved through the following technical solutions:
[0007] The present invention provides a method for determining printing parameters of a 3D printing sand mold, comprising the following steps:
[0008] Step S1, test sample preparation: printing a sand sample, and printing two eight-shaped test blocks at the same time, i.e., test block 1 and test block 2;
[0009] Step S2, determining the sand mold anisotropy according to the tensile strength ratio of test block 1 to test block 2;
[0010] Step S3, establishing a mathematical model of the relationship between sand mold strength and printing parameters;
[0011] Step S4: Based on the single factor control variable method, the data of sand mold strength under different printing parameters are obtained through experiments, and the regression parameter value of the mathematical model in step S3 is determined by linear fitting to obtain the linear regression equation of sand mold strength in different directions and printing parameters;
[0012] Step S5, based on the linear regression equation determined in step S4, determining the optimal printing parameters to achieve a strength ratio of the sand mold in different directions close to 1:1;
[0013] Step S6: According to the optimal printing parameters determined in step S5, the reliability of the linear regression equation is tested.
[0014] Furthermore, in step S1, the sand mold sample is a cylinder, the direction of the nozzle spraying binder is defined as the X direction, the direction perpendicular to the nozzle is defined as the Y direction, and the direction of layer-by-layer powder stacking is defined as the Z direction; the X direction is selected to represent the radial strength, and the Z direction represents the axial strength.
[0015] Further, in step S1, test block 1 is located at the top center of the sand mold, and the plane of test block 1 is parallel to the axial direction; test block 2 is located in the middle of the sand mold in the height direction, and the plane of test block 2 is parallel to the radial direction of the sand mold; the tensile strength of test block 1, that is, the tensile strength in the Z direction, is represented by the symbol σ1, and the tensile strength of test block 2, that is, the tensile strength in the X direction, is represented by the symbol σ2.
[0016] Furthermore, in step S1, the ply thickness is set to δ0 mm and the spray volume is set to V0 pL. In step S2, according to the ratio of the tensile strength of test block 1 to that of test block 2, the strength relationship between the X-direction and the Z-direction is established by data fitting, and formula (1) is obtained:
[0017] σ1=k0σ2 (1)
[0018] Among them, k0 is the ratio of the Z-direction tensile strength σ1 to the X-direction tensile strength σ2 of the same sand mold sample.
[0019] Furthermore, in step S3, the printing parameters include the liquid injection volume and the layer thickness. The tensile strength of the sand mold is taken as the dependent variable, and the liquid injection volume and the layer thickness are taken as the independent variables. A mathematical model is established to obtain formula (2):
[0020] σ∝αυ a δ b (2)
[0021] In formula (2), σ is the tensile strength in the Z direction or the tensile strength in the X direction, υ is the spray volume, δ is the ply thickness, α is the correction factor, a is the index related to the spray volume, and b is the index related to the ply thickness.
[0022] Further, step S4 includes the following steps:
[0023] Step S41: Establish the relationship between the spray volume v and the X-axis tensile strength σ2, and obtain formula (3):
[0024] σ2=σ v +k v (υ-V0) (3)
[0025] In formula (3), σ v is the tensile strength of specimen 2 when the spray volume is V0 pL, k v It is the ratio of the difference in tensile strength to the difference in spray volume at the maximum spray volume and the minimum spray volume, and υ is the spray volume.
[0026] Step S42: Establish the relationship between the ply thickness δ and the Z-direction tensile strength σ1, and obtain equation (4):
[0027] σ1=σ hv -k h (δ-δ0) (4)
[0028] In formula (4), σ hv is the tensile strength of specimen 1 when the ply thickness is δ0 mm, k h It is the ratio between the difference in tensile strength and the difference in ply thickness at the maximum and minimum ply thicknesses, and δ is the ply thickness.
[0029] Further, in step S41, the experimental data of L levels of the spray volume υ and the corresponding X-axis tensile strength σ2 are imported into the data simulation software for linear fitting to determine the slope k of equation (3): v .
[0030] Further, in step S42, the experimental data of L levels of ply thickness δ and the corresponding Z-direction tensile strength σ1 are imported into the data simulation software for linear fitting to determine the slope k of equation (4): h .
[0031] Furthermore, in step S5, the optimal process parameters are determined by adjusting the spray volume and the layer thickness parameters. The optimal process parameters satisfy:
[0032] σ2=σ v +k v (υ-V0)=σ1=σ hv -k h (δ-δ0).
[0033] Furthermore, in step S6, the optimal process parameters determined in step S5 are used to perform sand mold printing, and three figure-eight test blocks are arranged along the X, Y and Z directions respectively. The reliability of the linear regression equation in step S4 is tested based on the tensile strength ratio of the three test blocks.
[0034] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0035] (1) The eight-shaped test block of the present invention can be used as a representative of the mechanical properties in all directions of sand mold parts with complex shapes, high requirements for size and position accuracy, and high requirements for part surface quality. The eight-shaped test block can provide accurate parameters for the mechanical properties in all directions during the 3D printing process, which is conducive to quickly and accurately determining the anisotropy of the mechanical properties of the sand mold.
[0036] (2) The present invention comprehensively considers the printing direction of the sand mold test block when testing the strength of the 3D printed sand mold, thereby overcoming the problem that the traditional strength acceptance method does not consider the distortion of the measurement results and casting defects caused by different printing directions. The sand mold strength determination result provided by the present invention is more objective and scientific.
[0037] (3) The present invention uses a mathematical fitting method based on the strength ratio of the test blocks in different printing directions to find the law of the strength in different directions, so that the adjustment and determination of the printing parameters have a clear directionality.
[0038] (4) The present invention reveals the influence of two process parameters, namely, the volume of liquid sprayed and the thickness of the layer, on the tensile strength of the sand mold in different directions by constructing a mathematical model. Through the tensile test of the figure-eight test block, the linear regression equation of the constructed mathematical model can be obtained by conventional data simulation software when the number of tests is small. Furthermore, through verification, it is determined that the linear regression equation obtained by data simulation has a high degree of fit and reliability. This shows that the method for determining 3D printing parameters established by the present invention can efficiently determine the optimal process parameters of the 3D printing process, solves the problem in the prior art that the printing parameters cannot be determined quickly and accurately to achieve isotropic strength of the sand mold, helps to improve the controllability of the strength and other properties of the 3D printed sand mold, achieves the uniformity and quality stability of the overall strength of the sand mold, and reduces the occurrence of problems such as sand mold breakage.
[0039] (5) The 3D printing sand mold parameter determination method of the present invention can obtain the optimal process parameters conveniently, quickly and reliably. The optimal process parameters obtained by the parameter determination method of the present invention are used to perform 3D printing experiments, and sand mold parts with good isotropic consistency of mechanical properties can be obtained.
[0040] (6) The present invention has certain reference significance for the combination optimization problems of other similar process parameters (e.g., printing speed, resolution, etc.) in the 3D printing process, especially for the relevant performance (gas generation, air permeability, etc.) of 3D printing of slender pipe sand molds.
[0041] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the embodiments of the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0043] Figure 1 This is a schematic diagram of the structure of a 3D printing sand mold according to an embodiment of the present invention;
[0044] Figure 2 In the figure, (a) is a front view of the figure eight test block according to an embodiment of the present invention, and (b) is a side view of the figure eight test block according to an embodiment of the present invention;
[0045] Figure 3 It is a statistical diagram of the strength ratio of the test block 1 and the test block 2 according to the embodiment of the present invention.
[0046] Figure 4 It is a schematic diagram of a linear relationship established after performing regression analysis on the test of the influence of the spraying volume on the sand mold strength according to an embodiment of the present invention;
[0047] Figure 5 It is a schematic diagram of a linear relationship established after performing regression analysis on the test of the influence of the layer thickness on the sand mold strength according to an embodiment of the present invention;
[0048] Explanation of symbols:
[0049] 1-test block 1; 2-sand mold; 3-test block 2. DETAILED DESCRIPTION
[0050] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0051] The principle of the 3D printing sand mold printing parameter determination method adopted by the present invention is: during the printing process, by stacking layer by layer, each layer of silica sand is stacked, and a layer of binder droplets is sprayed by the print head. After the binder droplets drip onto the surface of the silica sand, they enter the gap between the silica sands and solidify, and finally form the sand mold shape and size set by the program. Due to the fluidity of the binder, the binder will be coated on the surface of the printed silica sand. In the single-layer printing state, the amount of binder coated around the printed silica sand will be relatively uniform. As the printing proceeds, under the action of the gravity of the sand mold, the thickness of the binder layer of the lower layer that is not completely solidified is affected by the increase in the weight of the upper sand mold and has a tendency to be compressed and thinned. When the printing layer thickness and the volume of the print head spray liquid remain unchanged, due to the fixed volume of the spray liquid between the layers, the thickness of the binder layer along the printing direction and the thickness of the binder layer perpendicular to the printing direction will be different, which is reflected on the sand mold, showing the difference in the binder content in different directions of the same thickness sand mold, and finally showing the difference in mechanical properties in different directions.
[0052] According to the characteristics of inconsistent strength of sand molds in different directions of 3D printed sand molds, two eight-shaped test blocks (i.e., test block 1 and test block 2) are set along the radial and axial directions of the sand mold while printing the sand mold. The tensile strength of the test blocks in the two directions is analyzed to determine the law of anisotropy of the sand mold. In order to achieve uniformity of strength in different directions, first, a mathematical model of the relationship between sand mold strength and printing parameters is established; then, based on the single-factor control variable method, the data of sand mold strength under different printing parameters are obtained through experiments, and these data points are linearly fitted to obtain the linear regression equation of radial and axial tensile strength of the sand mold and printing parameters; further, based on the linear regression equation, the optimal printing parameters are determined to achieve a tensile strength ratio of test block 1 to test block 2 close to 1:1, reduce the influence of anisotropy on the overall quality of the sand mold and the shrinkage rate of the casting, and achieve the consistency of shrinkage in all directions and dimensional stability during the solidification process of the casting.
[0053] Based on this principle and taking sand mold samples as research objects, the present invention proposes a method for determining printing parameters of 3D printing sand molds, comprising the following steps:
[0054] Step S1, test sample preparation: printing a sand sample, and printing two eight-shaped test blocks at the same time, namely, test block 1 and test block 2.
[0055] Print the sand sample, preferably, the sand sample is a cylinder; the printing direction is as follows Figure 1 The direction in which the nozzle moves to spray the binder is defined as the X direction, the direction perpendicular to the nozzle is defined as the Y direction, and the direction in which the powder is stacked layer by layer is defined as the Z direction; for the cylindrical sand mold, the strength in the X and Y directions is basically the same, the X direction is selected to represent the radial strength, and the Z direction represents the axial strength; the specific shape of the sand mold can be selected as needed, preferably but not limited to a cylinder, a cube, etc.
[0056] When printing the sand mold, two eight-shaped test blocks are printed at the same time for strength measurement, among which, test block 2 is located in the middle of the sand mold in the height direction, and the plane of test block 2 is parallel to the radial direction of the sand mold. Test block 1 is located at the top of the sand mold through the center, and the plane of test block 1 is parallel to the axial direction; among which, the tensile strength of test block 1 is represented by the symbol σ1, and the tensile strength of test block 2 is represented by the symbol σ2.
[0057] The printing adopts a flat paving method, setting the layer thickness to δ0mm and the spray volume to V0 pL; preferably, the spray volume is 100pL-200pL, the layer thickness is 0.1mm-0.6mm, the printing speed is 20s / layer-40s / layer, the specification of the sand in the sand mold is 70 mesh-140 mesh, and the spray volume is 100%.
[0058] It can be understood that the eight-shaped test block in step S1 can be used as a representative of the mechanical properties in all directions of sand mold parts with complex shapes, high requirements for size and position accuracy, and high requirements for part surface quality. The use of the eight-shaped test block can provide accurate parameters for the mechanical properties in all directions during 3D printing, which is conducive to quickly and accurately determining the anisotropy of the mechanical properties of the sand mold; at the same time, when detecting the strength of the 3D printed sand mold, the printing direction of the sand mold test block is comprehensively considered, which overcomes the disadvantage that the traditional strength acceptance method does not consider the distortion of the measurement results and casting defects caused by different printing directions. The determination result provided by the present invention is more objective and scientific.
[0059] Step S2, determining the sand mold anisotropy according to the tensile strength ratio of test block 1 to test block 2;
[0060] After printing, place it for N hours to ensure that the binder is completely hardened; then measure the tensile strength values of test block 1 and test block 2, and calculate the ratio of the tensile strength of test block 1 to test block 2, where the tensile strength of test block 1, i.e., the tensile strength in the Z direction, is represented by the symbol σ1, and the tensile strength of test block 2, i.e., the tensile strength in the X direction, is represented by the symbol σ2. The ratio of the tensile strength of test block 1 to test block 2 is the ratio of the tensile strength in the Z direction σ1 to the tensile strength in the X direction σ2. Repeat the experiment M times, and connect the ratios obtained from the M experiments on the coordinate axis. In the data simulation software, the average value and confidence interval of the tensile strength ratio are obtained by data fitting, and the relationship between the strength in the X and Z directions of the sand mold is obtained, and then the anisotropy of the sand mold strength is determined, which is the direction for adjusting the printing parameters in the next step to obtain isotropy. Specifically, the strength relationship between the X and Z directions is established, and formula (1) is obtained:
[0061] σ1=k0σ2 (1)
[0062] Among them, k0 is the ratio of the Z-direction tensile strength σ1 to the X-direction tensile strength σ2 of the same sand mold sample. When k0>1, the printing parameters can be adjusted to reduce σ1 or increase σ2 to achieve a ratio k0 close to 1; when 0<k0<1, the printing parameters can be adjusted to increase σ1 or reduce σ2 to achieve a ratio k0 close to 1.
[0063] It should be noted that after printing, the sample is left for N hours, and the value of N can be selected according to the type of adhesive and the size of the sample, etc. In this embodiment, N = 24. The experiment is repeated M times, and the value of M can be set as needed, preferably, M ≥ 5; in this embodiment, M = 5.
[0064] Furthermore, the confidence level of the confidence interval of the tensile strength ratio may be selected as required; in this embodiment, the confidence level is 95%.
[0065] It can be understood that in step S2, based on the strength ratio of the test blocks in different printing directions, a mathematical fitting method is used to find the law of the strength in different directions, so that the adjustment and determination of the printing parameters have a clear directionality.
[0066] Step S3, establishing a mathematical model of the relationship between sand mold strength and printing parameters;
[0067] Generally speaking, factors affecting the performance of 3D printed sand molds include layer thickness, liquid injection volume, printing speed, etc. These factors work together to affect the performance of 3D printed sand molds, including sand mold strength, gas emission, air permeability, etc. Among them, liquid injection volume and layer thickness are significant factors affecting sand mold strength. Therefore, the tensile strength of the sand mold is taken as the dependent variable, and the liquid injection volume and layer thickness are taken as independent variables to establish a mathematical model, and the formula (2) is obtained:
[0068] σ∝αv a δ b (2)
[0069] It should be noted that, in formula (2), σ is the tensile strength in the Z direction or the tensile strength in the X direction, v is the spray volume, δ is the ply thickness, α is the correction coefficient, a is an index related to the spray volume, and b is an index related to the ply thickness.
[0070] Step S4: Based on the single factor control variable method, the data of sand mold strength under different printing parameters are obtained through experiments, and the regression parameter value of the mathematical model in step S3 is determined by linear fitting to obtain the linear regression equation of sand mold strength in different directions and printing parameters;
[0071] Specifically, it can be seen from formula (2) that the influencing factors of the tensile strength in the Z direction or the tensile strength in the X direction σ mainly include two variables: the spray volume v and the ply thickness δ. For the problem of multiple factors (multiple variables), the method of controlling factors (variables) is used to turn the problem of multiple factors into multiple single-factor problems, and only one of the factors is changed, so as to study the influence of this factor on the strength of the test block, and study them separately, and finally solve them comprehensively, that is, the control variable method is used to study the relationship between the tensile strength in the X direction (σ2), the tensile strength in the Z direction (σ1) and the single factor;
[0072] Specifically, the steps include:
[0073] Step S41: It can be understood that as the spray volume increases, the penetration ability of the droplets increases, the diffusion in the X and Y directions is improved, the effective adhesive between the sand particles in the same layer increases, and the X-direction tensile strength σ2 is significantly improved; therefore, setting the spray volume is a significant factor affecting the X-direction tensile strength.
[0074] The control variable method is used to further determine the relationship between the spray volume and the tensile strength σ2 in the X direction. First, the ply thickness is kept constant at δ0, and the spray volume is adjusted by the droplet detection system. The droplet pulse parameters of different volumes are built into the printing system of the 3D printer, and the test block (i.e., block 2) is arranged and printed in the X direction. After the block 2 is printed, the tensile strength of the block 2 is measured by the sand mold strength tester; for example, the spray volume (unit pL) can be selected at L levels, i.e., V -2 、V -1 , V0, V1, V2…; preferably, L≥5, the difference between the L levels is the same, all are f; preferably, the value range of the spray volume v is 100pL-200pL; in this embodiment, V0=150pL, f=10pL, L=5, that is, the 5 levels are 130pL, 140pL, 150pL, 160pL, 170pL respectively.
[0075] Import the experimental data of L levels of the spray volume (v) and the corresponding X-direction tensile strength (σ2) into the data simulation software, with the spray volume (v) as the X-axis and the X-direction tensile strength (σ2) as the Y-axis, select "XY scatter plot", click the Finish button, and the original form of the scatter plot will appear;
[0076] Furthermore, the scatter plot is observed to determine whether the point series distribution has a linear trend; from the experimental results, the data has the characteristics of linear distribution. The linear regression analysis method is used to establish the relationship between the spray volume (v) and the X-axis tensile strength (σ2), and formula (3) is obtained:
[0077] σ2=σ v +kv (v-V0) (3)
[0078] In the formula, σ v is the tensile strength of specimen 2 when the spray volume is V0 pL, k v It is the ratio of the difference in tensile strength to the difference in spray volume at the maximum spray volume and the minimum spray volume, and v is the spray volume.
[0079] Furthermore, select the "Regression" option in the data simulation software, set the input area, confidence level and other parameters of the X and Y values, select the "Linear Fitting Graph" option, obtain the regression results, and read the "Slope k v "; Since step S2 is used to determine the anisotropy of the sand mold, the printing is based on V0 pL. In order to ensure the stability of the data, the tensile strength at V0 pL is selected as the calibration reference value. According to the "slope k v The mathematical model for the simple linear relationship between the spray volume (v) and the tensile strength in the X direction (σ2) was determined, and the linear regression equation (3) was obtained.
[0080] Step S42: It can be understood that, when the spraying volume remains unchanged, as the ply thickness increases, the distance between the layers increases, the effective adhesive between the layers decreases, and the Z-direction tensile strength σ1 decreases significantly. Therefore, setting the ply thickness is a significant factor affecting the Z-direction tensile strength σ1.
[0081] The control variable method is used to further determine the relationship between the ply thickness δ and the tensile strength σ1 in the Z direction. First, the spray volume V0 is determined to be constant, and the parameters of different ply thicknesses are built into the printing system of the 3D printer. The eight-shaped test block (i.e., test block 1) is arranged and printed in the Z direction. After the test block 1 is printed, the tensile strength of the test block 1 is measured using a sand mold strength tester. For example, the ply thickness δ (unit: mm) can be selected from L levels, i.e., …δ -1 , δ0, δ1, δ2, δ3…; preferably, L≥5, the difference between the L levels is the same, all are g; preferably, the value range of the layer thickness δ is 0.1mm-0.6mm; in this embodiment, δ0=0.25mm, g=0.1mm, L=5, that is, the 5 levels are 0.15mm, 0.25mm, 0.35mm, 0.45mm, and 0.55mm respectively.
[0082] Import the experimental data of L levels of ply thickness (δ) and the corresponding Z-direction tensile strength (σ1) into the data simulation software, with ply thickness (δ) as the X-axis and Z-direction tensile strength (σ1) as the Y-axis. Select "XY Scatter Plot" and click the Finish button. The original form of the scatter plot will appear.
[0083] Furthermore, the scatter plot is observed to determine whether the point distribution has a linear trend. From the experimental results, the data has the characteristics of linear distribution. The linear regression analysis method is used to establish the relationship between the ply thickness (δ) and the Z-direction tensile strength (σ1), and the formula (4) is obtained:
[0084] σ1=σ hv -k h (δ-δ0) (4)
[0085] In the formula, σ hv is the tensile strength of test block 1 when the printing thickness is δ0 mm, k h It is the ratio between the difference in tensile strength and the difference in ply thickness at the maximum and minimum ply thicknesses, and δ is the ply thickness.
[0086] Furthermore, select the "Regression" option in the data simulation software, set the input area, confidence level and other parameters of the X and Y values, select the "Linear Fitting Graph" option, obtain the regression results, and read the "Slope k h ", because in step S2, when determining the anisotropy of the sand mold, the printing is based on δ0mm, in order to ensure the accuracy of the data, the strength value at δ0mm is selected as the basic calibration value, according to the "slope k h The mathematical model for the simple linear relationship between the ply thickness (δ) and the tensile strength in the Z direction (σ1) is determined, and the linear regression equation (4) is obtained.
[0087] Step S5, based on the linear regression equation determined in step S4, determining the optimal printing parameters to achieve a strength ratio of the sand mold in different directions close to 1:1;
[0088] Specifically, the steps include:
[0089] Step S51: According to equations (1) and (3), the spray volume is adjusted while the ply thickness remains unchanged, and the resin content between the sand particles in the same layer is changed to achieve the purpose of adjusting the tensile strength of the test block 2. By adjusting the above parameters, the tensile strength ratio of the test block 1 to the test block 2 is close to 1:1, that is, σ2 = σ v +k v (v-V0) = σ1, to achieve the purpose of maintaining consistent shrinkage during solidification;
[0090] Step S52: According to equations (1) and (4), the spray volume is kept unchanged, that is, the effective binder volume between the same layers is kept unchanged, and the ply thickness is adjusted to change the tensile strength between the stacked layers, so as to achieve the purpose of adjusting the tensile strength of the test block 1, that is, σ1 = σ hv -k h (δ-δ0)=σ2, so that the tensile strength ratio of test block 1 to test block 2 is close to 1:1, and the purpose of maintaining consistent shrinkage during solidification is achieved;
[0091] Step S53: According to steps S51 and S52, the optimal printing parameter values (layer thickness, liquid injection volume) are determined so that the ratio of the tensile strength in the Z direction to the X direction is close to 1:1. The optimal process parameters satisfy:
[0092] σ2=σ v +k v (υ-V0)=σ1=σ hv -k h (δ-δ0).
[0093] Step S6: According to the optimal printing parameters determined in step S5, the reliability of the linear regression equation is tested.
[0094] Specifically, the optimal layer thickness and spray volume determined in step S5 are used as parameters for sand mold 3D printing to perform sand mold printing to obtain a 3D printed sand mold, and three figure eight test blocks are arranged along the X, Y and Z directions, that is, test block 1 is arranged and printed along the Z direction, test block 2 is arranged along the X direction, test block 3 is arranged and printed along the Y direction, test block 2 and test block 3 are located in the middle of the sand mold in the height direction, the planes of test block 2 and test block 3 are parallel to the radial direction of the sand mold, test block 1 is located at the top of the sand mold through the center, and the plane of test block 1 is parallel to the axial direction; after test block 1, test block 2 and test block 3 are printed, the tensile strength of test block 1, test block 2 and test block 3 is measured using a sand mold strength testing machine; according to the tensile strength ratio of the three test blocks, the reliability of the linear regression equation of step S4 is tested.
[0095] According to the test results, it is found that the ratio of the tensile strength in the X direction, the tensile strength in the Y direction, and the tensile strength in the Z direction is close to 1:1:1, which shows that the established linear regression equation has good fitting degree and high reliability. The optimal process parameters obtained by the parameter determination method in the present invention are used for 3D printing experiments, and sand mold parts with good isotropic consistency of mechanical properties can be obtained.
[0096] It should be noted that the data simulation software in steps S2 and S4 can be selected as needed, including but not limited to Excel, Origin, Matlab, etc. In this embodiment, Excel is selected as the data simulation software.
[0097] The 3D printing method in step S1 to step S6 can be selected as needed, including but not limited to fused deposition modeling (FDM), stereolithography (SLA), selective laser sintering / melting (SLS / SLM), three-dimensional printing process (3DP), etc. In this embodiment, the 3D printing method is a three-dimensional printing process (3DP).
[0098] It can be understood that step S3 reveals the influence of two process parameters, namely, the volume of liquid spraying and the thickness of the layer, on the tensile strength of the sand mold in different directions by constructing a mathematical model. In step S4, through the tensile test of the figure-eight test block, when the number of tests is small, the linear regression equation of the mathematical model can be obtained by using conventional data simulation software; based on the linear regression equation, the optimal printing parameters are determined through step S5; further, in step S6, it is verified that the linear regression equation has a high degree of fit and reliability, which shows that the 3D printing sand mold printing parameter determination method established by the present invention can efficiently determine the preferred process parameters of the 3D printing process, solves the problem in the prior art that the printing parameters cannot be quickly and accurately determined to achieve isotropy of sand mold strength, helps to improve the controllability of parameters such as the strength of 3D printed sand molds, achieve the uniformity and quality stability of the overall strength of the sand mold, and reduce the occurrence of problems such as sand mold breakage.
[0099] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments.
[0100] Example 1
[0101] Step S1: Use three-dimensional printing (3DP) technology to print a cylindrical sand mold, the diameter of the sand mold is 100 mm, the height is 200 mm, the binder is furan resin, and the sand specification in the sand mold is 100 mesh; the printing direction is as follows Figure 1 The direction in which the nozzle moves to spray the binder is defined as the X direction, the direction perpendicular to the nozzle is defined as the Y direction, and the direction in which the powder is stacked layer by layer is defined as the Z direction; for cylindrical sand molds, the strengths in the X and Y directions are basically the same, so the X direction is selected to represent the radial strength, and the Z direction represents the axial strength.
[0102] When printing the sand mold, two figure-eight test blocks are printed at the same time for strength measurement, wherein test block 2 is located in the middle of the height direction of the sand mold, and the plane of test block 2 is parallel to the radial direction of the sand mold; test block 1 is located at the top of the sand mold through the center of the circle, and the plane of test block 1 is parallel to the axial direction; wherein, the tensile strength of test block 1, i.e., the tensile strength in the Z direction, is represented by the symbol σ1, and the tensile strength of test block 2, i.e., the tensile strength in the X direction, is represented by the symbol σ2; the dimensions of the figure-eight test block are: 66 mm in length, 36 mm in width, 23 mm in thickness, the gauge length is 41 mm, and the width of the narrowest part in the middle is 23 mm.
[0103] The printing adopts a flat-laying method, with a layer thickness of 0.25 mm, a spray volume of 150 pL, a spray amount of 100%, and a printing speed of 30 s / layer (seconds / layer).
[0104] It should be noted that for the spray volume, the preferred value range is 100pL-200pL. The above range can avoid the resin droplet volume being too small, resulting in insufficient sand mold strength or the resin droplet volume being too large, causing deformation between sand particles due to sliding. In this embodiment, the middle value of 150pL in the above preferred range is selected as the basis to determine the anisotropy of the sand mold.
[0105] It should be noted that, for the layer thickness, due to the minimum printing layer thickness limit and the minimum strength limit of the 3D printer, preferably, the value range of δ is 0.1mm-0.6mm; it is understandable that if the layer thickness is too large, the tensile strength will be reduced and the minimum strength requirement of the casting will not be met. In this embodiment, according to the casting tolerance requirement of ±0.5mm, the maximum printing layer thickness required to achieve the casting size tolerance, that is, δ=0.25mm, is selected as the basis to determine the anisotropy of the sand mold.
[0106] Step S2: 24 hours after printing, measure the tensile strength of test block 1 and test block 2. The strength test machine model is YQY-Ⅱ, and the national standard for the test is GB / T2684-2009 Test method for sand machine mixture for casting; calculate the ratio of the tensile strength of test block 1 to that of test block 2, as shown in Table 1 below, and connect the ratio on the coordinate axis as shown in Table 1 below. Figure 3 As shown, according to the fact that the strength of test block 1 is greater than that of test block 2, it is determined that the amount of resin between the sand mold in the Z direction is greater than the amount of resin between the sand particles in the parallel direction of the same layer;
[0107] Table 1 Tensile strength and ratio of test block 1 and test block 2
[0108]
[0109] according to Figure 3 The ratio of tensile strength of test block 1 to test block 2 is basically between 1.44±0.18, among which the average value of the ratio of tensile strength is 1.44, the confidence interval is ±0.18, and the confidence level is 95%. The strength relationship between test block 1 and test block 2 is established, and formula (1) is obtained:
[0110] σ1=1.44σ2 (1)
[0111] It can be seen from formula (1) that the tensile strength σ1 in the Z direction of the sand mold is greater than the tensile strength σ2 in the X direction. In order to achieve a ratio close to 1:1, the optimal values of the printing parameters in the 3D printing process can be determined through the following steps S3-S5.
[0112] Step S3: Establishing a mathematical model of the relationship between sand mold strength and printing parameters;
[0113] The relationship between the tensile strength of the sand mold and the printing parameters (i.e., the injection volume and the layer thickness) in the 3D printing process is established as follows (2), where σ is the tensile strength in the Z direction or the tensile strength in the X direction, υ is the injection volume, δ is the layer thickness, α is the correction factor, a is the index related to the injection volume, and b is the index related to the layer thickness;
[0114] σ∝αυ a δ b (2)
[0115] Step S4: Based on the single factor control variable method, the data of tensile strength of the sand mold under different printing parameters are obtained through experiments, and the regression parameter value of the mathematical model in step 3 is determined by linear fitting to obtain the linear regression equation of the strength of the sand mold in different directions and the printing parameters;
[0116] Step S41: Using the control variable method, the thickness of the layer is controlled to remain unchanged. According to the casting tolerance requirement of ±0.5 mm, the maximum printing layer thickness is selected to achieve the casting size tolerance requirement, that is, δ = 0.25 mm. The spray volume is changed to verify the effect of the spray volume on the tensile strength σ2 of the sand mold in the X direction. The printing parameters and test results are shown in Table 2, and the data in Table 2 are connected on the coordinate axis as shown in Table 2. Figure 4 shown.
[0117] Table 2 X-axis tensile strength σ2 measurement results after changing the spray volume
[0118] Spray volumeυ / pL 130 140 150 160 170 <![CDATA[Tensile strength in the X direction σ2 / Mpa]]> 0.74 0.91 1.24 1.49 1.70
[0119] according to Figure 4 The tensile strength σ2 of the sand mold in the X direction increases with the increase of the spray volume. It is determined that the influence of the spray volume on the tensile strength σ2 in the X direction is positive, that is, a is determined to be positive, and through Figure 4 The simple linear relationship between the spray volume and the X-axis tensile strength σ2 is established using the data in the formula (3):
[0120] σ2=σ v +k v (v-150) (3)
[0121] In the formula, σ v k is the tensile strength of specimen 2 when the spray volume is 150 pL (i.e., tensile strength in the X direction), v It is the ratio between the difference in tensile strength in the X direction and the difference in the spray volume at the maximum spray volume and the minimum spray volume, and υ is the spray volume.
[0122] From Table 2 and Figure 3 It can be seen that the spray volume and the X-axis tensile strength σ2 are in a simple linear relationship. Through linear fitting with data simulation software, the slope k of the slope can be obtained. v=0.024Mpa / pL, then it can be known that the linear regression equation between the tensile strength in the X direction and the spray volume is: σ2=1.24+0.024(v-150), where υ is in pL; due to the relationship between the volume of the resin droplet and the sand particles, in order to avoid the resin droplet volume being too small to cause insufficient sand mold strength or the resin droplet volume being too large to cause deformation between the sand particles due to sliding, the value range of v in this formula is 100pL-200pL; since step S2 is used to determine the anisotropy of the sand mold, the printing is based on the spray volume V0 of 150pL, in order to ensure the stability of the data, the tensile strength at 150pL is selected as the calibration reference value.
[0123] It can be understood that as the spray volume increases, the penetration ability of the droplets increases, which improves the diffusion in the X and Y directions, increases the effective bonding agent between the sand particles in the same layer, and increases the tensile strength σ2 in the X direction.
[0124] Step S42: Using the control variable method, the spray volume is controlled to be constant, that is, v = 150 pL, and the layer thickness is changed to verify the effect of the layer thickness on the Z-direction tensile strength σ1 of the sand mold. The printing parameters and test results are shown in Table 3, and the data in Table 3 are connected on the coordinate axis as shown in Figure 5 shown.
[0125] Table 3 Z-axis tensile strength σ1 measurement results after changing the ply thickness
[0126] Layer thickness δ / mm 0.15 0.25 0.35 0.45 0.55 <![CDATA[Tensile strength in the Z direction σ1 / Mpa]]> 2.23 1.96 1.60 0.75 0.48
[0127] according to Figure 5 , the Z-direction tensile strength σ1 of the sand mold decreases with the increase of the ply thickness, and it is determined that the influence of the ply thickness on the Z-direction tensile strength σ1 of the sand mold is negative, that is, b is determined to be negative, and through Table 3 and Figure 5 Based on the data in the paper, a simple linear relationship between the layer thickness and the tensile strength σ1 of the printed sand mold in the Z direction is established, and formula (4) is obtained:
[0128] σ1=σ hv -k h (δ-0.25) (4)
[0129] In the formula, σ hv is the tensile strength of specimen 1 (i.e., tensile strength in the Z direction) when the ply thickness is 0.25 mm, k h is the ratio of the difference in tensile strength of specimen 1 to the difference in ply thickness when the maximum ply thickness is equal to that when the minimum ply thickness is equal to that of specimen 1, and δ is the ply thickness.
[0130] From Table 3 and Figure 5 It can be seen that when the spray volume remains unchanged, the tensile strength and the ply thickness are in a linear relationship. Through linear fitting with data simulation software, the slope k of the slope can be obtained. h=-4.4Mpa / mm, we can know the linear regression equation between the tensile strength in the Z direction and the layer thickness: σ1=1.96-4.4(δ-0.25), where δ is in mm; due to the minimum printing layer thickness limit and the minimum strength limit of the 3D printer, the value range of δ is 0.1mm-0.6mm; because in step S2, when determining the anisotropy of the sand mold, the printing is based on the maximum layer thickness of 0.25mm that ensures the casting size tolerance meets ±0.5mm. In order to ensure the accuracy of the data, the tensile strength value at 0.25mm is selected as the basic calibration value.
[0131] It can be understood that, when the spray volume remains unchanged, as the ply thickness increases, the distance between layers increases, the effective bonding agent between layers decreases, and the Z-direction tensile strength σ1 decreases accordingly.
[0132] Step S51: According to formula (1) and formula (3), the spray volume is adjusted while the ply thickness remains unchanged, and the resin content between the sand particles in the same layer is changed to achieve the purpose of adjusting the tensile strength of the test block 2 (i.e., the tensile strength in the X direction); through the above parameter adjustment, the tensile strength ratio of the test block 1 to the test block 2 is close to 1:1, that is, σ2=1.24+0.024(v-150)=σ1;
[0133] Step S52: According to formula (1) and formula (4), the spray volume is kept unchanged, that is, the effective binder volume between the same layers is kept unchanged, and the ply thickness is adjusted to change the tensile strength between the stacked layers, so as to achieve the purpose of adjusting the tensile strength of the test block 1 (that is, the tensile strength in the Z direction), and realize that the tensile strength ratio of the test block 1 to the test block 2 is close to 1:1, that is, σ1=1.96-4.4(δ-0.25)=σ2;
[0134] Step S53: According to steps S51 and S52, the optimal printing parameters are determined such that the ratio of the tensile strength in the Z direction to the X direction is close to 1:1, and the optimal process parameters satisfy: σ2=1.24+0.024(υ-150)=σ1=1.96-4.4(δ-0.25);
[0135] It should be noted that there are multiple sets of optimal printing parameter values that satisfy the above linear relationship equation σ2=1.24+0.024(υ-150)=σ1=1.96-4.4(δ-0.25); illustratively, the optimal printing parameters include but are not limited to:
[0136] Group 1: The layer thickness is 0.4 mm and the spray volume is 150 pL;
[0137] Group 2: The layer thickness is 0.3 mm and the spray volume is 170 pL;
[0138] The third group: the layer thickness is 0.5 mm and the spray volume is 140 pL.
[0139] Step S6: using the optimal process parameters determined in step S5, for example, a layer thickness of 0.4 mm and a liquid injection volume of 150 pL, as parameters for sand mold 3D printing to perform sand mold printing and obtain a 3D printed sand mold;
[0140] The obtained 3D printed sand mold was tested for all-directional tensile strength, and the results are as follows:
[0141]
[0142] According to the test results, the ratio of the tensile strength in the X direction, the tensile strength in the Y direction, and the tensile strength in the Z direction is close to 1:1:1. The optimal printing parameters determined by the method of the present invention are used to obtain a sand mold part with good consistency in all directions.
[0143] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for determining printing parameters of 3D printing sand molds, characterized in that: The following steps are involved: Step S1, test sample preparation: printing a sand sample, and printing two eight-shaped test blocks at the same time, i.e., test block 1 and test block 2; Step S2, determining the sand mold anisotropy according to the tensile strength ratio of test block 1 to test block 2; Step S3, establishing a mathematical model of the relationship between sand mold strength and printing parameters; Step S4: Based on the single factor control variable method, the data of sand mold strength under different printing parameters are obtained through experiments, and the regression parameter value of the mathematical model in step S3 is determined by linear fitting to obtain the linear regression equation of sand mold strength in different directions and printing parameters; Step S5, based on the linear regression equation determined in step S4, determining the optimal printing parameters to achieve a strength ratio of the sand mold in different directions close to 1:1; Step S6: According to the optimal printing parameters determined in step S5, the reliability of the linear regression equation is tested.
2. The method for determining printing parameters of 3D printing sand molds according to claim 1, characterized in that: In step S1, the sand mold sample is a cylinder, the direction of the nozzle spraying the binder is defined as the X direction, the direction perpendicular to the nozzle is defined as the Y direction, and the direction of layer-by-layer powder stacking is defined as the Z direction; the X direction is selected to represent the radial strength, and the Z direction represents the axial strength.
3. The method for determining printing parameters of 3D printing sand molds according to claim 2, characterized in that: In step S1, the test block 1 is located at the top center of the sand mold, and the plane of the test block 1 is parallel to the axial direction; the test block 2 is located in the middle of the sand mold in the height direction, and the plane of the test block 2 is parallel to the radial direction of the sand mold; the tensile strength of the test block 1, that is, the tensile strength in the Z direction, is represented by the symbol σ1, and the tensile strength of the test block 2, that is, the tensile strength in the X direction, is represented by the symbol σ2.
4. The method for determining printing parameters of 3D printing sand molds according to claim 3, characterized in that: In step S1, the layer thickness is set to δ0 mm and the spray volume is set to V0 pL. In step S2, according to the ratio of the tensile strength of test block 1 to that of test block 2, the strength relationship between the X-direction and the Z-direction is established by data fitting, and formula (1) is obtained: σ1=k0σ2 (1) Among them, k0 is the ratio of the Z-direction tensile strength σ1 to the X-direction tensile strength σ2 of the same sand mold sample.
5. The method for determining printing parameters of 3D sand mold according to claim 4, characterized in that: In step S3, the printing parameters include the liquid injection volume and the layer thickness. The tensile strength of the sand mold is taken as the dependent variable, and the liquid injection volume and the layer thickness are taken as the independent variables. A mathematical model is established to obtain formula (2): σ∝αv a d b (2) In formula (2), σ is the tensile strength in the Z direction or the tensile strength in the X direction, υ is the spray volume, δ is the ply thickness, α is the correction factor, a is the index related to the spray volume, and b is the index related to the ply thickness.
6. The method for determining printing parameters of 3D printing sand molds according to claim 5, characterized in that: The step S4 comprises the following steps: Step S41: Establish the relationship between the spray volume υ and the X-axis tensile strength σ2, and obtain formula (3): σ2=σ v +k v (u-V0) (3) In formula (3), σ v is the tensile strength of specimen 2 when the spray volume is V0pL, k v It is the ratio of the difference in tensile strength to the difference in spray volume at the maximum spray volume and the minimum spray volume, and υ is the spray volume. Step S42: Establish the relationship between the ply thickness δ and the Z-direction tensile strength σ1, and obtain equation (4): σ1=σ hv -k h (d-d0) (4) In formula (4), σ hv is the tensile strength of specimen 1 when the ply thickness is δ0 mm, k h It is the ratio between the difference in tensile strength and the difference in ply thickness at the maximum and minimum ply thicknesses, and δ is the ply thickness.
7. The method for determining printing parameters of 3D sand mold according to claim 6, characterized in that: In step S41, the experimental data of L levels of the spray volume υ and the corresponding X-axis tensile strength σ2 are imported into the data simulation software for linear fitting to determine the slope k of equation (3): v .
8. The method for determining printing parameters of 3D sand molds according to claim 7, characterized in that: In step S42, the experimental data of L levels of ply thickness δ and the corresponding Z-direction tensile strength σ1 are imported into the data simulation software for linear fitting to determine the slope k of equation (4): h .
9. The method for determining printing parameters of 3D printing sand molds according to claim 8, characterized in that: In step S5, the optimal process parameters are determined by adjusting the spray volume and the layer thickness parameters. The optimal process parameters satisfy: σ2=σ v +k v (υ-V0)=σ1=σ hv -k h (δ-δ0).
10. The method for determining printing parameters of 3D sand mold according to claim 9, characterized in that: In step S6, the optimal process parameters determined in step S5 are used to perform sand mold printing. At the same time, three figure-eight test blocks are arranged along the X, Y and Z directions respectively. The reliability of the linear regression equation in step S4 is tested based on the tensile strength ratio of the three test blocks.
Citation Information
Patent Citations
Selective laser sintering sand mold and scanning method thereof
CN113878089A
3D printing equipment
CN115090832A
Method for optimizing sand mold 3D printing parameters
CN116579138A
Casting method of integrated automobile aluminum alloy chassis and automobile aluminum alloy chassis
CN118045956A
Ingot making method
JP2014159041A